2013
DOI: 10.1155/2013/491657
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eating Disorders in Adults with Celiac Disease

Abstract: Background. Symptoms of celiac disease negatively impact social activities and emotional state. Aim was to investigate the prevalence of altered eating behaviour in celiac patients. Methods. Celiac patients and controls completed a dietary interview and the Binge Eating Staircases, Eating Disorder Inventory (EDI-2), Eating Attitudes Test, Zung Self-Rating Depression Scale, State Trait Anxiety Inventory Forma Y (STAI-Y1 and STAI-Y2), and Symptom Check List (SCL-90). Results. One hundred celiac adults and 100 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 29 publications
2
50
1
6
Order By: Relevance
“…Planning and preparing food should not dominate thoughts and dictate behaviours above and beyond that of other daily activities (24) . Recent research on disordered eating in CD indicates that both extreme GFD adherence and dietary transgressions are associated with disordered eating patterns (26)(27)(28)(29)(30)(31)(32) . For those who fail to adhere to their GFD, the challenges of managing the GFD may lead to restrictive or bulimic eating behaviours (31)(32)(33) .…”
Section: Introductionmentioning
confidence: 99%
“…Planning and preparing food should not dominate thoughts and dictate behaviours above and beyond that of other daily activities (24) . Recent research on disordered eating in CD indicates that both extreme GFD adherence and dietary transgressions are associated with disordered eating patterns (26)(27)(28)(29)(30)(31)(32) . For those who fail to adhere to their GFD, the challenges of managing the GFD may lead to restrictive or bulimic eating behaviours (31)(32)(33) .…”
Section: Introductionmentioning
confidence: 99%
“…At the onset, patients may present typical manifestation (diarrhea, weight loss), may be oligosymptomatic, or may present atypical symptoms such as headache and psychiatric disturbances,1 including eating disorders (EDs) 2. Anorexia nervosa (AN) is one of the most common psychiatric diagnoses in adolescent girls (<1%–4% of the female population).…”
Section: Introductionmentioning
confidence: 99%
“…Even within this subset of undiagnosed individuals with pathological CD, research has found altered eating behaviors [50]. In all, eating pathology has been demonstrated to be more common in young women living with CD compared to young men with CD and healthy controls [50].…”
Section: Ed Risk Factors Associated With CDmentioning
confidence: 99%